Transforming Indonesia’s Omnichannel E-Commerce Strategy: Driving Consumer Channel Choice in The Digital Shopping Era - Kenny Fernando; Renny Christiarini (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rapid growth of omnichannel retail has transformed consumer shopping behavior by integrating online and offline channels, yet inconsistencies in service, trust, and satisfaction remain critical challenges for retailers. The focus of this study is to find out what influences omnichannel selection intention and word of mouth mediated by perceived trust and satisfaction. Usually using random sampling procedures, quantitative research methods include sending surveys and examining certain populations or samples with quantitative data. Respondents in this study were 270 consumers who had utilized omnichannel services in Indonesia. The results of the study show that omnichannel service convenience and omnichannel congruence have a significant positive effect on perceived trust. Then, omnichannel service convenience and omnichannel congruence have a significant positive effect on satisfaction. Then perceived trust has a significant positive effect on omnichannel selection intention, satisfaction, and word of mouth. Omnichannel service convenience and omnichannel congruence have a significant positive effect on omnichannel selection intention mediated by perceived trust. Omnichannel congruence has a significant positive effect on word of mouth mediated by perceived trust. Satisfaction does not have a significant effect on word of mouth. Omnichannel service convenience has a significant positive effect on word of mouth mediated by satisfaction.